Impact of Illuminant Metamerism on Colour Fidelity in Graphic Reproduction of Artistic Images - Albulena Bilalli; Igor Zjakić (Tehnički Glasnik, 2024)
The aim of the research was to to evaluate the quality of illuminant metamerism by using Colour rendering index through similar paintings and half-tone reproduction images within the graphic industry. Employing the methodology of visual perception and testing conducted by standard observers, the study scrutinises how different colour techniques of paintings respond to diverse light sources under standardised conditions. This investigation is pivotal for understanding the chromatic fidelity and consistency of paintings and their reproduction with half-tone colours, by measuring the grey balance field, for all images. To find the most suitable light source and to complete the colour quality, the Osram LED light at 3000 K, 4000 K, and 6500 K is used. The resulting index could be deceptive in cases of significant disparities. The American IES TM-30-18 colour rendering index (CRI) metric, quantifies illumination metamerism's ability to faithfully depict natural colours. At every stage (R1–R15), the average colour reproduction CRI must be more than 90.